Prospective performance evaluation of selected common virtual screening tools. Case study: Cyclooxygenase (COX) 1 and 2 - Kaserer, Teresa; Temml, Veronika; Kutil, Zsofia; Vanek, Tomas; Landa, Premysl; Schuster, Daniela (European journal of medicinal chemistry, 2015)
Computational methods can be applied in drug development for the identification of novel lead candidates, but also for the prediction of pharmacokinetic properties and potential adverse effects, thereby aiding to prioritize and identify the most promising compounds. In principle, several techniques are available for this purpose, however, which one is the most suitable for a specific research objective still requires further investigation. Within this study, the performance of several programs, representing common virtual screening methods, was compared in a prospective manner. First, we selected top-ranked virtual screening hits from the three methods pharmacophore modeling, shape-based modeling, and docking. For comparison, these hits were then additionally predicted by external pharmacophore- and 2D similarity-based bioactivity profiling tools. Subsequently, the biological activities of the selected hits were assessed in vitro, which allowed for evaluating and comparing the prospective performance of the applied tools. Although all methods performed well, considerable differences were observed concerning hit rates, true positive and true negative hits, and hitlist composition. Our results suggest that a rational selection of the applied method represents a powerful strategy to maximize the success of a research project, tightly linked to its aims. We employed cyclooxygenase as application example, however, the focus of this study lied on highlighting the differences in the virtual screening tool performances and not in the identification of novel COX-inhibitors.
Keywords: Molecular Structure; Models, Molecular; Cyclooxygenase Inhibitors; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; cyklooxygenasa 1; vztah mezi dávkou a účinkem léčiva; Cyclooxygenase 2; Drug Evaluation, Preclinical; Cyclooxygenase 1; Humans; preklinické hodnocení léčiv; inhibitory cyklooxygenasy; cyklooxygenasa 2; lidé; Structure-Activity Relationship; molekulární modely; molekulární struktura